The Effect of ESG Practices on Corporate Tax Avoidance: Evidence from Non-Financial Firms in Indonesia - Maretta Yoehana; Cynthia Afriani Utama (Greenation Research & Yayasan Global Resarch National, 2026)
This study analyzes the effect of Environmental, Social, and Governance (ESG) performance on corporate tax avoidance among non-financial firms listed on the Indonesian Stock Exchange during 2015–2024. Based on stakeholder theory, companies with stronger ESG practices are expected to engage in lower tax avoidance due to higher commitments to transparency, accountability, and stakeholder interests. Using a quantitative approach, this research applies panel data regression to 463 firm-year observations. Tax avoidance is measured by the Cash Effective Tax Rate (CETR), reflecting actual cash tax payments relative to pre-tax income, while ESG data are sourced from Refinitiv’s LSEG database. The analysis employs the Fixed Effects Model (FEM) and the First Difference Generalized Method of Moments (FD-GMM) to address potential endogeneity. The FEM results show no significant relationship between ESG and CETR. However, FD-GMM findings indicate a positive and significant effect, suggesting that better ESG performance leads to higher cash tax payments and lower tax avoidance. Overall, the results emphasize that ESG plays an important role in shaping corporate tax behavior, although the relationship is sensitive to the estimation method used.